After broadcast news : Media regimes, democracy and the new information environment - Williams, Bruce A.; Dello Carpini, Michael X., 1953- (Cambridge, United Kingdom Cambridge University Press, 2011)
Conté: Machine generated contents note: Is there a difference between Tina Fey and Katie Couric?: policing the boundaries between news and entertainment -- Media regimes and American democracy -- And that's the way it (was): the rise and fall of the age of broadcast news -- Political reality, political power and political relevance in the changing media environment -- Politics in the emerging new media age: hyperreality, multiaxiality, and 'the Clinton scandals' -- When the media really matter: coverage of the environment in a changing media environment -- 9/11 and its aftermath: constructing a political spectacle in the new media environment -- Shaping a new media regime<U+000d><U+000a>"The new media environment has challenged the role of professional journalists as the primary source of politically relevant information. After Broadcast News puts this challenge into historical context, arguing that it is the latest of several critical moments in which the relationship among citizens, political elites, and the media has been contested"--National Library of Canada<U+000d><U+000a>"Most people assume that professional jounalists are the ligitimate source for political information and the role of "good" citizens is to watch, read or listen to the news. In After the News we show that this particular model is only one among several that have existed in the United States; that while it had some valuable aspects, it also had very narrow notions of what kind of information was politically relevant and what the role of citizen should be; and that the new information environment (from the internet to The Daily Show) make these strengths and limitations clear"--National Library of Canada
Keywords: Medios de comunicación social -- EEUU; Democracia -- EEUU